Depot- and obesity-related differences in adipogenesis. (October 2012) - Lessard, Julie; Tchernof, André
Adipocyte hypertrophy and hyperplasia are known to facilitate lipid storage in adipose tissues by increasing adipocyte cell size and number, respectively. Adipogenesis is the process resulting in adipose tissue hyperplasia. Although depot-specific differences and obesity-related modulation of adipocyte size are well documented, available data on adipogenesis and adipose tissue hyperplasia are less conclusive. Most studies support a reduction of adipogenesis in the obese state. Preadipocytes of the subcutaneous fat depot appear to be more responsive to adipogenic stimulation compared with those from visceral fat compartments in most studies. A number of studies support the notion that adipose tissue expansion through hyperplasia reduces ectopic lipid excess and obesity-related complications. Several genetic variants have been identified in the genes coding for adipogenesis-regulating proteins. While some of these variants have been clearly associated with the phenotypes of obesity and obesity-related alterations, available data highlight the importance of considering gene–gene and gene–diet interactions.